Skeletal muscle derived Musclin protects the heart during pathological overload - Malgorzata Szaroszyk; Badder Kattih; Abel Martin-Garrido; Felix A. Trogisch; Gesine M. Dittrich; Andrea Grund; Aya Abouissa; Katja Derlin; Martin Meier; Tim Holler; Mortimer Korf-Klingebiel; Katharina Völker; et al. (Nature Communications, 2022)
Cachexia is associated with poor prognosis in heart failure. Here the authors show that mice and patients with cardiac cachexia display reduced skeletal muscle expression and circulating levels of Musclin. Musclin ablation in skeletal muscle worsens, while its muscle-specific overexpression ameliorates heart failure in mice.